1998
DOI: 10.1046/j.1526-4610.1998.3805352.x
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic Innervation of the Human Dura Mater Involved in Headache

Abstract: The catecholaminergic innervation of cranial dura mater in humans was studied by examining several dural zones (vascular, perivascular, intervascular) in different regions (basal, calvarial, occipital, frontal, tentorial, parietal, temporal). The results demonstrate that catecholaminergic nerve fibers are present in human cranial dura mater and that these fibers, after exposure to formaldehyde vapors, show the specific fluorescence of catecholamines. There are more dural catecholaminergic nerve fibers in the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Using fluorescence techniques, Cavalloti et al (2) found that the cranial dura mater contains extensive sympathetic innervation. This finding is based on the principle that exposure of the dural mater to formaldehyde vapors causes catecholaminergic fibers to fluoresce.…”
Section: Sympathetic Innervation Of the Cranial Duramentioning
confidence: 99%
See 2 more Smart Citations
“…Using fluorescence techniques, Cavalloti et al (2) found that the cranial dura mater contains extensive sympathetic innervation. This finding is based on the principle that exposure of the dural mater to formaldehyde vapors causes catecholaminergic fibers to fluoresce.…”
Section: Sympathetic Innervation Of the Cranial Duramentioning
confidence: 99%
“…Unfortunately, the specific types of catecholaminergic fibers have not been elucidated (6). Cavallotti et al (2) concluded that all sympathetic fibers present in the cranial dura mater originate from the superior cervical ganglion, hypothesizing that the vasoconstrictor role of such sympathetic fibers may be implicated in the pathology of headache (2). Keller et al (7) confirmed that sympathetic fibers innervating the superior sagittal sinus of the rat and other areas of the supratentorial dura mater originated from the superior cervical ganglion.…”
Section: Sympathetic Innervation Of the Cranial Duramentioning
confidence: 99%
See 1 more Smart Citation
“…When the vasoconstrictor activity of D2 receptors is blocked, blood flow increases. In the light of the results of previous studies, 13,19 the presence of D1 and D2 receptors in the wall of the rat dura mater vessels appears significant.…”
Section: Discussionmentioning
confidence: 78%
“…2) [32]. Catecholaminergic fibers from the dura also originate from the superior cervical ganglion of the sympathetic chain [33]. Although the innervation of the dura cannot readily be interrupted with extracranial nerve blocks, knowledge of these pathways is still important for relieving pain during awake intracranial surgery.…”
Section: Pain and Intracranial Surgerymentioning
confidence: 99%